2016
DOI: 10.1038/srep32330
|View full text |Cite
|
Sign up to set email alerts
|

A Na+ Superionic Conductor for Room-Temperature Sodium Batteries

Abstract: Rechargeable lithium ion batteries have ruled the consumer electronics market for the past 20 years and have great significance in the growing number of electric vehicles and stationary energy storage applications. However, in addition to concerns about electrochemical performance, the limited availability of lithium is gradually becoming an important issue for further continued use and development of lithium ion batteries. Therefore, a significant shift in attention has been taking place towards new types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
164
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(177 citation statements)
references
References 35 publications
12
164
1
Order By: Relevance
“…Our theory also reveals the underlying origin for the enhancement in bulk conductivity observed in previous doped NaSICON materials, [27][28][29][30] in which the Na +ion concentration increases as a compenstation of the aliovalent doping (Zn 2+ , Ca 2+ , Ba 2+ , Y 3+ , Sc 3+ ) at the Zr site. This finding supports the results of theory described above, which suggests that the Na + -ion concentration is a main factor determining the bulk conductivity in NaSICON materials.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Our theory also reveals the underlying origin for the enhancement in bulk conductivity observed in previous doped NaSICON materials, [27][28][29][30] in which the Na +ion concentration increases as a compenstation of the aliovalent doping (Zn 2+ , Ca 2+ , Ba 2+ , Y 3+ , Sc 3+ ) at the Zr site. This finding supports the results of theory described above, which suggests that the Na + -ion concentration is a main factor determining the bulk conductivity in NaSICON materials.…”
supporting
confidence: 56%
“…[21][22][23] The total ion conductivity varies by an order of magnitude with x and the highest value (0.67 mS cm −1 at 300 K) was reported in the monoclinic phase where x ≈ 2.0, that is, Na 3 Zr 2 Si 2 PO 12 . [28][29][30] Guin and Tietz [31] reviewed various substituted NaSICONtype materials and concluded that the optimum ion conductivity is achieved at a Na + -ion content of ≈3.3 mol formula unit −1 . Researchers have primarily focused on using doping strategies to further improve the conductivity of this system, with Sc-substituted Na 3.4 Sc 0.2 Zr 1.8 (SiO 4 ) 2 (PO 4 ) exhibiting the highest reported conductivity at room temperature (6.2 mS cm −1 for the bulk value and 4.0 mS cm −1 for the total value, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have already been carried out to develop a suitable RT solid electrolyte material. [13][14][15][16] In this regard nonoxide chalcogenide glasses (Na 2 (Ga 0.1 Ge 0.9 ) 2 14 In general, NASICON and the relevant solid electrolytes are produced using a conventional solid state reaction process, which includes sintering and calcination over 1100 C. 22 The sintering process usually leads to the formation of voids and may disturb the development of new structured materials to gain high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…These last few years, efforts on novel electrode and electrolyte materials successfully yielded room‐temperature battery devices . New NASICON (Na/Zr/Mg‐based silicate‐phosphate) exhibits high room‐temperature ionic conductivity σ = 3.5 × 10 −3 S cm −1 . However, most commercially developed sodium‐based accumulators rely on a sodium‐sulfur electrochemical cell operated around 320 °C with liquid Na and liquid S as positive and negative electrodes respectively, separated by β‐alumina (Na 2 O‐11Al 2 O 3 ) as solid electrolyte .…”
Section: Introductionmentioning
confidence: 99%